Membatik Jumputan untuk Keluarga Ibu-Ibu PKK RW 02 Kelurahan Baktijaya, Kecamatan Sukmajaya, Depok (Neolectura, 2021)
Batik is a craft that has high artistic value and has become part of Indonesian culture which is a legacy of the ancestors of the Indonesian nation which has been widely known in the world. The potential of batik can be used to foster interest in the archipelago's literature, as a historical heritage that is still admired by all levels of society. One of the relics that is also strategic to be developed is wastra jumputan. One of the easier and faster batik fabrics to make and will be easily learned by the public. This jumputan batik training was applied to the families of RW 02 PKK women, Baktijaya Village, Sukmajaya District, Depok. This jumputan batik training was a follow-up to the previous training which was only held at the RT level. Through training with video recording tutorials and online methods, it will be one method of growing public interest in recognizing and developing the potential of Indonesian literature without having to meet in person. The results of the training show that the most prominent interest in jumputan batik is the motifs it produces. Various motifs can be produced with several manufacturing techniques that are relatively easy to master by the trainees. With the Covid-19 pandemic, this batik training is not like before, which is in one place but at home each and also followed by the families of PKK mothers by following the instructions we have given. As the end result of this effort, people who initially did not know or had followed this method of making jumputan wastra, in just two hours the community could master it well in producing various jumputan cloth motifs.